Land of milk and honey [large type] - Zhang, C Pam (Thorndike Press large print top shelf., 2024)
"A smog has spread. Food crops are rapidly disappearing. A chef escapes her dying career in a dreary city to take a job at a decadent mountaintop colony seemingly free of the world's troubles. There, the sky is clear again. Rare ingredients abound. Her enigmatic employer and his visionary daughter have built a lush new life for the global elite, one that reawakens the chef to the pleasures of taste, touch, and her own body. In this atmosphere of hidden wonders and cool, seductive violence, the chef's boundaries undergo a thrilling erosion. Soon she is pushed to the center of a startling attempt to reshape the world far beyond the plate"--Back cover.